Classics in Scientific ManagementDel MarDonald and CollonsRodger D. (Eds.). Classics in Scientific Management (University, Ala.: University of Alabama Press, 1976), 444 pp., $17.50. - Wren, Daniel A. (Academy of Management Review, 1977)
This article presents a review of the book ?Classics in Scientific Management,? edited by Donald Del Mar and Rodger D. Collons.